Comparative study of the antioxidant and enzyme inhibitory activities of two types of Moroccan Euphorbia entire honey and their phenolic extracts - Boutoub, Oumaima (2021)
Honey is a natural food product very famous for its health benefits for being an important source of antioxidant and phenolic compounds. Euphorbia honeys obtained from different regions of Morocco were evaluated for their ability to inhibit acetylcholinesterase, lipoxygenase, tyrosinase and xanthine oxidase activities. Their antioxidant properties were evaluated using the: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging capacity, nitric oxide scavenging activity (NO) and scavenging ability of superoxide anion radical. Then, the phenolic extracts of the same entire honey samples were evaluated by liquid chromatography coupled to diode array detection and mass spectrometry (LC-DAD-MS) and tested for the biological activities previously evaluated on the entire honeys, in order to conduct a comparative study between both (honey and phenolic extracts). The chromatographic profiles for the studied Euphorbia honey extracts were different. Phenolic compounds gallic acid, 4-hydroxybenzoic acid and p-coumaric acid were detected in all samples, whereas kampferol was only present in two samples. Physicochemical parameters and total phenolic content were also determined. Entire honey that recorded the highest rate of phenols was sample M6 (E. resinifera) = 69.25 mg GAE/100 g. On the other hand, the phenolic extracts had better antioxidant and enzyme inhibitory activities than the entire honeys, regardless the monofloral honey type. In conclusion, the studied Euphorbia honeys may have a great potential as antioxidant, anti-inflammatory and anti-tyrosinase sources for pharmaceutical and cosmetic applications.